2020
DOI: 10.33394/jss.v3i1.3681
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Effect Review of Agarwood Leaves From Aquilaria and Gyrinops Genera

Abstract: Aquilaria and Gyrinops are the most common genera of Agarwood in Indonesia. These two group have wide distribution in Indonesia. Therefore, Indonesia is one of the biggest agarwood commodity producer in the world. However, the resin on agarwood stem is still main utilization of agarwood commodity in this country. Diversification agarwood utilization other than resin is needed to maximilize the potency of this commodity. Agarwood leaves are one of by product from agarwood cultivation that rarely been utilized. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
2
0
2
Order By: Relevance
“…According to the Chinese Pharmacopoeia, the content of alcohol-soluble extracts in agarwood should not be less than 10% [66]. In addition, the content of alcohol-soluble essential oil serves as one of the guiding indicators for the classification of agarwood in the trading market and is also an important indicator for judging the quality of agarwood within the agarwood industry [67][68][69]. Studies have shown that the use of fungal inoculants can effectively increase the yield and quality of Agarwood after induction.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Chinese Pharmacopoeia, the content of alcohol-soluble extracts in agarwood should not be less than 10% [66]. In addition, the content of alcohol-soluble essential oil serves as one of the guiding indicators for the classification of agarwood in the trading market and is also an important indicator for judging the quality of agarwood within the agarwood industry [67][68][69]. Studies have shown that the use of fungal inoculants can effectively increase the yield and quality of Agarwood after induction.…”
Section: Discussionmentioning
confidence: 99%
“…Berdasarkan prioritas pemilihan bahan baku teh herbal, dalam kegiatan pengabdian ini dipilih 4 jenis TOGA potensial untuk dijadikan teh herbal. Keempat TOGA tersebut adalah: jambu biji (Díaz- de-Cerio et al, 2017), Sereh (Nambiar & Matela, 2012), kelor (Gopalakrishnan et al, 2016, dan gaharu (Wangiyana, 2020). Kegiatan pengabdian kepada masyarakat ini bertujuan untuk melatih ibu PKK di kelurahan Tanjung Karang untuk mengolah daun TOGA menjadi teh herbal sebagai salah satu bentuk PHC untuk pencegahan infeksi COVID-19 di lingkungan keluarga.…”
Section: Pendahuluanunclassified
“…Pengenalan khasiat medis dari TOGA tersebut diharapkan mampu mendorong partisipan untuk mulai menoptimalkan pemanfaatannya dalam menjaga kesehatan keluarga. Secara singkat, ringkasan khasiat medis TOGA yang • Membantu mengatasi penyakit saluran pencernaan (Wangiyana, 2020) Khasiat medis yang bervariasi dari TOGA yang dingunakan dalam kegiatan pengabdian ini memungkinkan partisipan untuk memilih aplikasi teh herbal TOGA sesuai dengan kebutuhan. Mereka juga dapat memilih jenis TOGA mana yang lebih disukai oleh keluarga mereka dari segi rasa.…”
Section: Hasil Dan Pembahasanunclassified
“…Aquilaria sinensis, in particular, contains the active ingredient flavonoid glycoside, which acts as an anti-inflammatory agent by inhibiting the production of pro-inflammatory agents, specifically Reactive Nitrogen Species, produced by macrophage cell lines (11). Previous research has highlighted the presence of alkaloids, flavonoids, and triterpenoids compounds in agarwood leaves of the Aquilaria malaccensis species, demonstrating their role in the healing process of burn wounds (12,13).…”
Section: Introductionmentioning
confidence: 99%